EFFECT OF PHOSPHATE FERTILIZER TYPE AND ITS LEVELS ON GROWTH, AND YIELD OF WHEAT (Triticum aestivum L.) IN A GYPSIFEROUS SOIL - Hammada, Ayad A.; Khalefah, Khalaf M.; Khalaf, Aiad A. (Diyala Agricultural Sciences Journal, 2017)
Afield experiment was conducted in a sandy loam texture to study effect of phosphate fertilizer type and its levels on growth and yield of wheat (Triticum aestivum L.) in a gypsiferous soil. The experiment was conducted according to Randomized Complete Block Design (RCBD) with three replications used two types of phosphate fertilizers (TSP-Triple Super Phosphate and DAP- Di Ammonium Phosphate(. Phosphorus fertilizer was applied in six levels (0, 20, 40, 60, 80 & 100) kg P ha-1 with symbols P1, P2, P3, P4, P5 and P6. The total plots were 36 experimental units. Nitrogen fertilizer added to all treatments at a rate of 200 kg N ha-1 in Urea form (46% N) applied at agriculture and at 45 days after germination. Potassium fertilizer added at rate of 165 kg K ha-1 in the form of potassium sulfate(43% K). The results showed significant increased (plant height, spike number, spike weight, straw and grains yield) in all parameters for both fertilizer types. Results refer TSP fertilizer better than DAP fertilizer in the growth criteria's and yield components